Ideen und Interessen. Zum Verhältnis von Religion und wirtschaftlicher Entwicklung - Deutschmann, Christoph (Ideas and interests. On religion and economic development, 2013)
While concentrating on the rise of modern capitalism, Weber’s seminal studies have little to say about the impact of religions on contemporary economic development. The paper comments about recent approaches to find an answer to the questions Weber left open. If one disregards a priori constructions of culturalist and rational-choice-theories, these approaches end up again in restating the circular relationship between ideas and interests showed already by Weber, albeit clearly with a higher emphasis on interests. However, the author argues that it would be premature to interpret this result simply as a confirmation of Weber’s “disenchantment” thesis. Rather, it goes back to the transformation of the economy itself into an entity that preaches “values”, proclaims “visions” and in this sense develops an affinity to religious movements. The author deepens this view by referring to Marx’ and Polanyi’s interpretation of capitalism as a system of disembedded markets. The disembedding of markets gives rise to a historically new potential of social uncertainty which the actors need to cope with, thereby developing symbolisms showing striking affinities with religious forms. Nevertheless, the analogies between capitalism and religion are limited. (English)
Sociology
Keywords: Entgrenzung; Institutionen; Kontingenz; Märkte; Säkularisierung; WEBER; Max; 1864-1920; Werte; capitalism; capitalism - religious aspects; consumption (economics); contingency; disembedding; economic aspects; economic development; institutions; markets; philosophy; religion; religion and sociology; religious aspects; secularization; values

From Economy to Society: Perspectives on Transnational Risk Regulation - Lange, Bettina; Thomas, Dania; Sarat, Austin (Emerald Group Publishing, 2013)
This special issue asks what role society can play in the regulation of transnational risks, as an alternative to or at least significant addition to reliance on state regulatory activity and the myth of the self-regulatory capacity of markets (Stiglitz, 2001, p. xiii). How can a social sphere contribute to the prevention and management of risks, often transnational in nature, posed by economic activity? Leading socio-legal scholars explore whether and how the idea of harnessing the regulatory capacity of a social sphere provides a new analytical lens that can provide fresh insights into transnational risk regulation, and whether this idea helps to identify innovative approaches to regulating transnational risks. KM - Parts I and II theoretically equgage specifically with Polanyi, and apply and develop Polanyian ideas.
Law; Sociology
Keywords: administrative law & regulatory practice; commercial law; comparative law; embeddedness; emotions; international law; international trade law; risk; self-regulating market

Transforming Capitalism: The Triple Crisis - Kirby, Peadar (Irish Journal of Sociology, 2013)
This article identifies a triple crisis of capitalism based on the three fictitious commodities as identified by Karl Polanyi: labour, money and land. This framework is used to integrate the environmental crisis into the wider crisis of capitalism. It argues that international actions required to reduce greenhouse gas emissions are going to present major challenges for capitalism with implications for the current dominance of market power and the subservience of state and social power. The article critically examines the potential of climate capitalism to achieve a low-carbon society by 2050 and introduces the need to face the challenges of degrowth.
Sociology; Political Science
Keywords: climate capitalism; climate change; de-growth; degrowth; development models; fictitious commodities; sustainability

Capitalism: restless and unbounded? Some neo-Polanyian and Schumpeterian reflections - Harvey, Mark; McMeekin, Andrew (Economics of Innovation & New Technology, 2013)
This paper first explores the notion that the limitlessness of knowledge is a privileged source of the restlessness of capitalism [Metcalfe, J. S. 2001. “Institutions and Progress.”Industrial and Corporate Change10 (3): 561–586; 2002. “Knowledge of Growth and Growth of Knowledge.”Journal of Evolutionary Economics12 (1): 3–13; 2004. “The Entrepreneur and the Style of Modern Economies.”Journal of Evolutionary Economics14 (2): 157–175; 2010. “University and Business Relations: Connecting the Knowledge Economy.”Minerva48 (1): 5–33] when combined with incentives of entrepreneurialism in a market society. Metcalfe gives a central paradigm of evolutionary economics a distinctive turn, with knowledge the pre-eminent source of variation, and markets the primary arena of selection. The paper engages this approach with a neo-Polanyian approach of ‘instituted economic process’, in which the variation and selection dynamic is itself seen as instituted within a particular historical economic context. The paper develops a critique of the evolutionary paradigm firstly by suggesting variations in instituted ‘economies of knowledge’ within a multi-modal conception of capitalism. Further breaking with the bipolar variation-selection paradigm, the paper argues that there has been a significant role of the state as a distinctive source of variation and selection in innovation and economic transformation. This leads us finally to analyse the shifting place of economy in society and polity, and the strategic responses in the USA, Brazil and Europe to the historically novel conjuncture of peak oil and global climate change, as a further source of variation. We conclude that a choice between evolutionary and historical approaches to innovation and economic transformation is a false one, once a universalising and unbounded paradigm of variation and selection is abandoned.
Sociology
Keywords: SCHUMPETER; Joseph Alois; 1883-1950; capitalism; economic development; entrepreneurship; evolution; evolutionary economics; instituted economic process; mixed economy; multi-modality; organizational change; variation and selection

The Politics of Dispossession: Theorizing India’s “Land Wars” - Levien, Michael (Politics & Society, 2013)
While struggles over land dispossession have recently proliferated across the developing world and become particularly significant in India, this paper argues that existing theories of political agency do not capture the specificity of the politics of dispossession. Based on two years of ethnographic research on anti-dispossession movements across rural India, the paper argues that the dispossession of land creates a specific kind of politics, distinct not just from labor politics, but also from various other forms of peasant politics that have been theorized in the social sciences. It illustrates how the process of land dispossession itself shapes the targets, strategy and tactics, organization, social composition, goals, and ideologies of anti-dispossession struggles. It concludes with reflections on why land conflicts are less easily institutionalized than labor conflicts and may therefore constitute a significantly disruptive force in the emerging centers of global capitalism for the foreseeable future.
Sociology; Political Science
Keywords: India; accumulation by dispossession; agrarian change; agriculture; capitalism; eviction; land grabs; peasant politics; peasants; property rights; social movements

From the Great Transformation to the Great Financialization: On Karl Polanyi and Other Essays - Polanyi Levitt, Kari (Zed Books, 2013)
Four years into the unfolding of the most serious crisis since the 1930s, Karl Polanyi's prediction of the fateful consequences of unleashing the destructive power of unregulated market capitalism on peoples, nations, and the natural environment have assumed new urgency and relevance. Polanyi's insistence that 'the self-regulating market' must be made subordinate to democracy otherwise society itself may be put at risk is as true today as it was when Polanyi wrote. Written from the unique perspective of his daughter, From the Great Transformation to the Great Financialization is an essential contribution to our understanding of the evolution and contemporary significance of Karl Polanyi's work, and should be read against the background of the accelerating accumulation of global finance that created a series of financial crises in Latin America, Russia, Asia, and, eventually, the heartlands of capitalism itself.
Political Science; Sociology
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Latin America; business & economics; economic conditions; economic development; economic history; global financial crisis; political economy; political science

Polanyi in an Hourglass: The Two Lives of a Sociological Classic - Frerichs, Sabine (Studies in Law, Politics & Society, 2013)
This article aims to show that studies of transnational risk regulation can benefit from Polanyian and neo-Polanyian research agendas in the field of law, economy, and society. Risk regulation would then be under-stood as a corrective force within the market society. Drawing on the relevant literature in the field, Karl Polanyi's work is contextualized both in the past ("scholarship before and beside Polanyi") and in the present ("scholarship after and beyond Polanyi"). The review considers developments within sociology, its neighboring disciplines economics and jurisprudence, and the interdisciplinary research fields of "economy and society," "law and society," and "law and economy." The article demon-strates that Polanyi is a "late classic" who shares the holistic orientation of classical historical scholarship. At the same time, it is argued that his "early revival" is due to the topicality of his criticism of the market society, and its inherent risks, in an era of neoliberalism and globaliza-tion. By going back and forth in time, the article situates Polanyi in a line of holistically minded scholarship that combines insights of general, economic, and legal sociology in what can be called the "economic sociol-ogy of law." This is "old" and "new," at the same time.
Sociology
Keywords: classical sociology; contemporary sociology; economic sociology; economic sociology of law; general review; interdisciplanary research; law and economics; market society; neoliberalism; risk regulation; sociological research

After a Romantic Aspiration to Society: Harnessing the Regulatory Capacity of a Social Sphere - Lange, Bettina (Studies in Law, Politics & Society, 2013)
This introduction unpacks the key question that informs the articles in this special issue. How does a social sphere inform regulation and, more specifically, how can the regulatory capacity of a social sphere be har-nessed, as an alternative or significant complementary force to state reg-ulation and reliance on the self-regulatory capacity of markets? This question is salient and topical also in light of the search for new regula-tory strategies and perspectives in the aftermath of the 2007 financial and subsequent EU sovereign debt crises, which have led to a major rea-lignment of economy and society in a number of countries. This introduction argues that economic sociology is a crucial reference point for understanding more about the social practices that constitute business behavior. It enables to explore the scope and significance of often interlinked social and legal norms for regulating various transna-tional risks that economic activity can give rise to. The introduction therefore locates the quest for understanding more about the regulatory capacity of a social sphere in debates that draw on Karl Polanyi's analy-sis of the embedding, disembedding, and re-embedding of economic activ-ity into social norms. The introduction highlights one of the key themes developed in this special issue, the idea of society within economy which questions an assumed conceptual distinction between economy and society. This introduction concludes by specifying how the accounts of risk regu-lation developed in this special issue chart a path that is different from recent explorations of the role of a social sphere in regulation, which were conducted under the banner of "the sociological citizen," "regula-tory sociability," and "collaborative governance."
Law; Sociology
Keywords: European Sovereign Debt Crisis; 2009-; European Union; crisis; economic sociology; economic sociology of law; financial crisis; international business enterprises; regulation; social sphere; socio-legal studies; state regulation; transnational risk

From Polanyi to Discourse Theory - Lange, Bettina (Studies in Law, Politics & Society, 2013)
This article starts from the assumption that economic sociology, including Karl Polanyi's work, can contribute fresh perspectives to regulation debates because it opens up new understandings of the nature of economic activity, a key target of legal regulation. In particular this article examines Polanyi's idea that society drives regulation. For Polanyi the "regulatory counter-movement" is society's response to the disembedding – in particular through the proliferation of markets – of economic out of social relationships. Section One of the article identifies three key chal-lenges that arise from this Polanyian take on regulation for contempor-ary regulation researchers. First, Polanyi focuses on social norms restraining business behavior, but neglects social norms embedded in law as also shaping regulation. Second, he seems to imply a clear-cut concep-tual distinction between "economy" and "society." Third, his analysis sidelines the role of interest politics in the development of regulation. Addressing the first of these three key challenges, Section Two of this article therefore argues that a Polanyian vision of "socialized" legal reg-ulation should build on contemporary accounts of responsive law and reg-ulation, which focus attention on social norms informing legal regulation. Section Three of this article tackles the second key challenge raised by Polanyi's work for contemporary regulation researchers, that is, how to transcend a modernist perspective of "economy" and "society" as clearly demarcated, distinct fields of social action. It argues that discourse the-ory is an important alternative theoretical resource. Drawing on Laclau and Mouffe, the article suggests that understanding "economy" and "society" as performed by open and relationally constructed discourses helps to capture interconnections between "economy" and "society" that become particularly visible when we analyze how specific regulatory regimes work at a medium- and small-scale level. These points are further brought to life in Section Four through a discussion of the European Union (EU) regulatory regime for trade in risky, transgenic agricultural products, and in particular the current reform debates about the consideration of the "socioeconomic impacts" of such products.
Law; Sociology
Keywords: European Union; European Union regulation; discourse theory; economic sociology; embeddedness; embedding theorems; responsive regulation; socio-economic impacts; socioeconomics; transgenic agricultural products

A Systems Theory Perspective on Polanyi's Great Transformation: The Case of Financial Derivative Contracts - Paterson, John (Studies in Law, Politics & Society, 2013)
Whereas much of the renewed interest in Polanyi's Great Transform-ation speculates that the rebalancing of economy and society he foresaw might now be emerging in the context of the financial crisis, the systems theory perspective adopted in this article concludes that there are good reasons to believe that such a shift may be no closer. From an examina-tion of credit default swaps and corporate bonds, the article suggests that finance may best be understood as an internally differentiated subsystem of the economy and thus perhaps peculiarly proof against efforts to exert control over it. Concluding that Polanyi's analysis lacks the conceptual tools to cope with contemporary conditions when compared to systems theory, the article nevertheless suggests that his approach may usefully be extended by adding a fourth fictitious commodity - risk – to the familiar trio of land, labor, and money.
Sociology
Keywords: POLANYI; Karl; 1886-1964; contracts; corporate bonds; derivatives; economic aspects; economic sociology; economy; markets; prices; society; swaps (finance); systems theory

Trust and Regulation: Insights from the Mining Industry - Schiavi, Petrina (Studies in Law, Politics & Society, 2013)
This article develops Polanyi's (2001) theme of harnessing the regula-tory capacity of a social sphere by focusing on trust as an emotion for framing risk regulatory regimes. Using the global mining sector as its focus, it explores the role of trust in the regulation and corporate man-agement of social and environmental risk Sociological perspectives on trust are employed to identify and analyze dynamics of trust in the mining industry. The article draws on data col-lected between 2004 and 2008 by way of participant observation, docu-ment analysis, and in-depth qualitative interviews with around 40 representatives of the mining industry, NGOs, and regulators. Trust-rela-tionships are an example of harnessing the regulatory capacity of a social sphere, but they can also undermine regulatory effort where trust is abused. The effectiveness of trust-based regulation would be enhanced by sanctions for nonperformance that target corporate motivations and financial performance. This research focused on a selection of large, multinational mining corporations with a presence in Australia. Generalizations could not be made from this research about smaller mining entities or single-country or state-owned corporations. A better understanding of corporate trust-building behaviors and motiva-tions can help inform more effective regulatory strategy for improving corporate, social, and environmental impacts. This article contributes to the body of knowledge about the regulation of the social and environmen-tal performance of the mining industry. This is important as many of the remaining accessible mineral deposits across the globe are in areas of environmental and social significance.
Sociology; Law
Keywords: POLANYI; Karl; 1886-1964; corporate responsibility; delegated legislation; environmental risk assessment; financial risk; mineral industries; mining industry; regulation; risk; social responsibility of business; trust

"Etiquette and Magic": Between Embedding and Embedded Corporate Social Responsibility - Voiculescu, Aurora (Studies in Law, Politics & Society, 2013)
This article looks at corporate social responsibility (CSR) as a discur-sive social practice that attempts to interrogate the global market econ-omy and its neoliberal underpinnings and that reflects as well as frames and shapes domestic and global politics and institutions. Drawing upon Karl Polanyi's notions of reciprocity and redistribution while also emphasizing the normative content of the concept, the article inquires into the position that the CSR discourse occupies in addressing the cor-porate transnational risks derived from social tensions and conflicts and more generally, in answering social expectations for justice. The Polanyian perspective highlights the CSR discursive quest for a missing conceptual consistency and implicitly, for a constructive "critical" core. From this perspective, the article shows CSR to reside within controver-sial conceptual boundaries; a discursive social practice that engages with the social aspiration of embedding market economy in society while it is also in need of reclaiming its critical core and its potential for social change.
Sociology; Law
Keywords: civil economy; corporate social responsibility; embedding theorems; neoliberalism; reciprocity (commerce); reciprocity and redistribution; social change; social embeddedness; social responsibility of business; socio-legal studies

Pi̇yasa: Adam Smith Versus Karl Polanyi̇ - Gökten, Yeliz SARIÖZ (Academic Review of Economics & Administrative Sciences, 2013)
In this study author will try to make comparative analysis of Adam Smith and Karl Polanyi's ideas about market. According to Smith market is a mechanism which allocating resources through invisible hand. Contrary to Smith, Polanyi, asserts that a market is a intervention style to economy. Intervention is an inherent property of market. In the first part of this study Adam Smith's opinions about market which assings limited duty to state and defends social interest will come true through invisible hand will be examined. Second part will concentrate on Karl Polanyi's arguments against appear of market society and market economy. At the end of the study, the author has tried to analyse two different market conceptualization and to assert how well this approaches to understand our times. (English)
Economics; Sociology
Keywords: Piyasa; Piyasa Sistemi; SMITH; Adam; 1723-1790; comparative studies; economic research; economists; market; market system

The Institution, the Economy and the Market: Karl Polanyi's Institutional Thought for Economists - Maucourant, Jerome; Plociniczak, Sebastien (Review of Political Economy, 2013)
This paper aims to clarify the logical structure of Karl Polanyi's concept of institution, especially with regard to his most important contribution to political economy—the conception of self-regulating markets as institutions. Although Polanyi did not provide a well-developed concept of institution, this article argues that such a concept exists in his work. Moreover, there is in Polanyi's work a sophisticated institutionalist account of the self-regulating market that has been largely overlooked as Polanyi does not present it explicitly. Analyzing the economy as an institutionalized process, as Polanyi does, reveals that the market is neither a natural nor a spontaneous phenomenon—a conclusion that runs counter to conventional economic thinking. Polanyi's approach enables us to view capitalism (the ‘market society’ in Polanyi's language) through a highly specific cultural fact: the fiction of the self-regulating market. This institutional perspective needs to be reassessed beyond new-institutionalist theoretical constructions.
Economics; Sociology
Keywords: economic structure; free enterprise; institutions (philosophy); philosophy of economics; social facts

Rudderless in a Sea of Yellow: The European Political Economy Impasse for Renewable Transport Energy - Harvey, Mark; Pilgrim, Sarah (New Political Economy, 2013)
Faced with the twin challenges of anthropogenic climate change and ‘peak oil’, the need for an urgent and radical transformation of transport energy has been widely recognised. Adopting a neo-Polanyian economic sociology approach, this article asks what conditions European governance capacity to respond to these challenges, at either national or regional levels, using biofuels as a case study. It asks if the complexity of its political institutions, and the heterogeneity of interests and economic organisations, present ‘the biggest obstacle of all’ (Cohen 2007) to reduce fossil fuel dependency. By examining the European Commission level and comparing five countries, evidence is produced for a political failure in terms of continued fossil fuel dependency. Incumbent interests in the agricultural sector and a distinctively European legacy of a transport fleet dependent on fossil diesel, have led to a marriage of convenience between rapeseed farmers and vehicle manufacturers. As a consequence, rather than escaping from the path dependency on fossil fuels (Unruh 2000), Europe has gone down a cul-de-sac of rapeseed biodiesel inherently limited in scope, and with the low levels of greenhouse gas emissions savings. Ironically this outcome is in part an unintended consequence of opposition to biofuels from environmentalist groups and politics.
Sociology; Biology
Keywords: agriculture; biodiesel fuels; biofuels; biomass energy research; climate change; climate change research; economics; peak oil; politically instituted markets; rapeseed

Towards an Economic Sociology of Law - Ashiagbor, Diamond; Kotiswaran, Prabha; Perry-Kessaris, Amanda (Wiley-Blackwell, 2013)
Reflecting a developing trend towards interdisciplinary research in economics and law, this agenda–setting volume makes the case for economic sociology of law an emerging field that draws on empirical, analytical and normative insights from sociology to investigate relationships between legal and economic phenomena. It locates this novel subject in a wider socio–legal tradition and identifies common ground between Polanyian and Weberian approaches to the law, economy, and society, despite the two theorists divergent views on the functionality of the capitalist model. The volume provides a platform for researchers critical responses to the social embeddedness of market societies. Contributors demonstrate the value of applying a combination of methods in their work, from heterogeneous disciplines such as legal history and ethnography. They consider the position in the western and developed nations, as well as in post–colonial polities. The resulting publication is a well–crafted primer on a specialism that, by combining the insights of socio–economic analysis with the formative influences exerted by their specific legal contexts, informs a more nuanced assessment of law, economics and society.
Law; Sociology
Keywords: WEBER; Max; 1864-1920; economic sociology; economic sociology of law; law

Rethinking ‘Embeddedness’: Law, Economy, Community - Cotterrell, Roger (Journal of Law and Society, 2013)
Ideas (of Karl Polanyi and others) that economies and markets are ‘socially embedded’ are central to recent research in economic sociology, closely paralleling socio-legal claims for studying law in ‘social context’. But the concept of embeddedness is imprecise and inadequate: a sociology of law and economy cannot rely on it but must address intellectual and moral-political concerns that its use reflects. Max Weber's writings on law and economy have inspired advocates of a new economic sociology of law, but some of Weber's key claims may be outdated, and he treats law and economy as distinct spheres rather than as facets of the social. Sociological research on law and economy should focus on ‘networks of community’ and their regulation, thus illuminating the social character of both law and economic relations. Viewing the social (including economic life) through a ‘community lens’ makes it possible to analyse cultural factors in regulating markets, while emphasizing links between economic relations and other aspects of social life.
Law; Sociology
Keywords: embeddedness

Law, Social Policy, and the Constitution of Markets and Profit Making - Veitch, Kenneth (Journal of Law and Society, 2013)
This article explores the relationship between law, society, and economy in the context of the contemporary British welfare state. Drawing on themes in Polanyi's The Great Transformation, it identifies the constitutive role of contemporary social policy and law in the creation and maintenance of markets and opportunities for the private sector in the field of welfare, focusing on the institutional mechanisms being put in place to encourage this. What emerges is a reformulation of the function of the welfare state and related law, as these are no longer predominantly driven by a logic of social protection via redistribution to those in need, but increasingly reflect the state's desire to create openings for the private sector within welfare. The institutions that once contributed to ensuring the embeddedness of the market economy in society now play an important role in processes of disembedding – with potentially detrimental consequences for those seeking assistance from the welfare state.
Law; Sociology
Keywords: Great Britain; disembeddedness; welfare state

A More Perfect Commodity: Bottled Water, Global Accumulation, and Local Contestation - Jaffee, Daniel; Newman, Soren (Rural Sociology, 2013)
Bottled water sits at the intersection of debates regarding the social and environmental effects of the commodification of nature and the ways neoliberal globalization alters the provision of public services. Utilizing Polanyi's concept of fictitious commodities and Harvey's work on accumulation by dispossession, this article traces bottled water's transformation from elite niche item to a product consumed by three fourths of U. S. households. Drawing on ethnographic research with participants in two cases of proposed spring water extraction from rural communities by industry leader Nestlé Waters, we make two principal arguments. First, the case of bottled water necessitates a reevaluation of existing theoretical frameworks regarding water privatization and commodification. Municipal tap water networks pose substantial barriers to capital accumulation, leading one influential scholar to frame water as an 'uncooperative commodity.' However, bottled water's characteristics enable it to evade many of these constraints, rendering it a 'more perfect commodity' for accumulation. Second, expansion of the market good of bottled water alters the prospects for the largely publicly provided good of tap water. We conclude that the growth of this relatively new commodity represents a more serious threat to the project of universal public drinking water provision than that posed by tap water privatization.
Sociology
Keywords: HARVEY; David; bottled water; commercial products; drinking water; ethnographic analysis; fictitious commodities; globalization; households; municipal services; primitive accumulation; privatization; research

Decommodification and Welfare State: the Case of Workplace Accident Victims - Tabin, Jean-Pierre; Probst, Isabelle; Waardenburg, George; Dransart, Dolores Angela Castelli; Pasche, Geneviève; Bolzman, Claudio (Dekommodifizierung und Wohlfahrtsstaat: der Fall von Opfern von Arbeitsunfällen., 2013)
To what extent does the social treatment of workplace injury in Switzerland enable victims to be decommodified in the sense given by Gøsta Esping-Andersen (1990) to this concept, i.e. enable them to leave the labor market in a way that allows them to uphold a socially acceptable standard of living? After a sociological discussion about the concept of decommodification, we present the results of a qualitative study conducted in Switzerland about workplace accident victims and show that the kind of index proposed by Esping-Andersen in order to compare welfare states is based on a faulty premise. (English)
Sociology
Keywords: Arbeitsunfall; POLANYI; Karl; 1886-1964; Schweiz; Suisse; Switzerland; Wohlfahrtsstaat; accident du travail; accident insurance; commodification; cost & standard of living; decommodification; dekommodifizierung; démarchandisation; kommodifizierung; labor laws & legislation; labour laws & legislation; marchandisation; qualitative research; welfare state; work-related injuries; workplace accident; état social

Karl Polanyi - Vail, John (Routledge, 2013)
Economics; Sociology
Keywords: business & economics / economics / theory

Nationalist Politics and the Double Movement: The Problem of Legitimacy in Neoliberal States - Blad, Cory (Conference Papers – American Sociological Association, 2013)
This paper argues that the contemporary efficacy of nationalist politics is a strategic response to neoliberal conditions of state legitimation. Using the double movement as a theoretical framework, I argue that neoliberalism alters the policy alternatives available to state actors by reducing the viability of economic protectionist initiatives once dominant in the embedded liberal era. This policy capacity reduction inhibits some of the key means for state legitimation (e.g., public spending, regulatory protectionism), which exacerbate the negative effects of capitalist liberalization. As national populations view the state as unwilling or unable to mitigate economic adversities or provide traditional socio-economic services, significant potential exists for a delegitimation of state actors and institutions. In response, neoliberal state actors have gravitated toward an increasingly cultural rhetoric of nationalism as a means to maintain popular legitimacy. This shift goes beyond simple political power struggles - in accordance with the double movement framework, systemic global capitalism requires legitimate state authority to ensure both local stability and sustained capital accumulation. Neoliberal ideology, however, discourages traditional means of state legitimation. A Polanyian examination of this ironic condition offers a structural explanation for the increased efficacy of nationalist politics; however, it also raises serious questions about the sustainability of this legitimation strategy.
Sociology
Keywords: double movement; globalization; nationalism; neoliberalism; state legitimation

Economic support personal networks of rural entrepreneurships - Cid-Aguayo, Beatriz E.; Sandoval-Nazal, Daniel; Carrasco, Juan Antonio (Conference Papers – American Sociological Association, 2013)
The Polanyian discussion about the embeddedness of the economy in social relations, finds a new stream through the social network analysis, from which is possible to map the cooperation relations that underlie economic ones. From the latter, this article shows the analysis of nine family-based economic entrepreneurships linked to a cooperative of services and agrofood products. Through personal networks analysis we mapped and highlighted the diversity of collaborations, monetary and non-monetary exchanges the entrepreneurships perform with their networks. In consequence, we characterized the support networks identifying the different economic exercises that take part in relation to the entrepreneurships. By this way, we accounted some relevant aspects such as the formality or informality condition, the entrepreneurships level, the networks' cohesion and the types of exchange, among other issues.
Sociology
Keywords: embeddedness; rural entrepreneurships; social networks

Marxism After Polanyi - Burawoy, Michael (Marxisms in the 21st Century: Crisis, Critique and Struggle, 2013)
KM - What should we do with Marxism ? For most the answer is simple. Bury it ! Mainstream social science has long since bid farewell to Marxism. The approach adopted here is that Marxism is a living tradition that enjoys renewal and reconstruction as the world it describes and seeks to transform undergoes change ... However, Marxsm cannot simply mirror the world. It seeks to change the world, but changing such a variegated world requires a variegated theory that keeps up with the times and accommodates places.
Sociology
Keywords: MARX; Karl; 1818-1883; Marxism; fictitious commodities

Europe and Problems of Marketization: from Polanyi to Scharpf - Crouch, Colin (Firenze University Press, 2013)
The author uses the theory of the 'Great Transformation' of the industrialisation of England developed by Karl Polanyi to describe the current situation in Europe. There is a strong marketisation of the economy and also of social life, but what is missing is the social policy that needs to accompany this process, if there are not to be major problems. From this perspective marketization and social policy do not exist in a zero-sum game, but are mutually dependent. The emphasis on negative rather than positive integration (to use the terms conceived by Fritz Scharpf) in the development of Europe makes this interdependence more difficult to achieve. The division of competences between the European level (market policies) and the nation states (social policies) makes this situation even worse. The only way forward is a strengthening of the European social dimension.
Sociology; Political Science
Keywords: Europe; business & economics; commodification; economic theory; social policy

Insurgency and institutionalization: the Polanyian countermovement and Chinese labor politics - Friedman, Eli (Theory and Society, 2013)
Why is it that in the nearly 10 years since the Chinese central government began making symbolic and material moves towards class compromise that labor unrest has expanded greatly? In this article I reconfigure Karl Polanyi's theory of the coutermovement to account for recent developments in Chinese labor politics. Specifically, I argue that countermovements must be broken down into two constituent but intertwined "moments": the insurgent moment that consists of spontaneous resistance to the market, and the institutional moment, when class compromise is established in the economic and political spheres. In China, the transition from insurgency to institutionalization has thus far been confounded by conditions of "appropriated representation," where the only worker organizations allowed to exist are those within the state-run All China Federation of Trade Unions. However, in drawing on two case studies of strikes in capital-intensive industries in Guangdong province, I show that the relationship between insurgency and institutionalization shifted between 2007 and 2010.
Sociology; Labor Studies
Keywords: ACFTU; China; countermovement; economic capital; insurgency; labor; labour; social movements

Formas De Integração E ‘Tríade Mercantil’: O Carácter Não Ontológico Do Mercado Na Análise Institucional De Karl Polanyi (Forms of Integration and ‘Catallactic Triad’: The Non-ontological Character of Market in the Institutional Analysis of Karl Polanyi) - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2013)
A análise da economia enquanto processo instituído, proposta por Polanyi, concretiza-se no estudo dos padrões institucionais que esta pode assumir empiricamente: reciprocidade, redistribuição e troca mercantil. Esta última – corporizada num sistema de mercados autorregulados – apenas se assume como forma de integração dominante nas sociedades capitalistas modernas. O estudo das formas de integração – assim como a sua extensão lógica à análise dos conceitos de comércio, dinheiro e mercado – permitirá que as ciências sociais evitem uma visão marcada pela ‘mentalidade de mercado’, ou ‘falácia economicista’. Se o comércio e o dinheiro têm acompanhado a humanidade desde os seus primórdios, os mercados são um desenvolvimento institucional bem mais recente.The analysis of the economy as instituted process, suggested by Polanyi, consists in the study of the institutional patterns which the economy may assume empirically: reciprocity, redistribution and market exchange. The last one – embodied in a system of price-making markets – only comes to be a dominant form of integration in modern capitalist societies. The study of the forms of integration – as well as its logical extension to the analysis of the concepts of trade, money and market – will allow social sciences to avoid a framework characterized by a ‘market mentality’, or ‘economistic fallacy’. Trade and money have existed since the early stages of mankind but markets are a more recent institutional development. in Teoria & Sociedade, Forthcoming
Sociology
Keywords: exchange; market; reciprocity; redistribution